The study of educational and didactic works (For the example of "The knowledge of the box", "Hibat ul haqoyiq", "The Nightmare") - Zaripova Dilfuza Bakhtiyorovna (Proceedings of The ICECRS, 2019)
This article makes analyses of the research on well known that during the Oriental Renaissance. The main problem in the spiritual and educational sphere was the human problem. Therefore, great attention is paid to education. In the didactic works, the moral, spiritual and moral development of the Eastern man is at the forefront. The idea of humanity and human dignity has been the cornerstone of education. It is important to implement education, which builds on high moral values, human relationships and traits as the main means of implementing this idea. Conclusion of the research makes outcomes and shortcomings to make better analyses in further.